Naravna radioaktivnost kot vir energije za življenje - Drozdek, Tinka (Matrika, 2023)
Living microorganisms have been found in water samples taken deep below the Earth’s surface. Some of them have been isolated from the surface for over one billion years. Most of them had the genetic record for the production of enzymes that can obtain life energy from the synthesis of hydrogen. Among the more important findings is the fact that large amounts of hydrogen are produced by radiolysis of water. This means that natural ionizing radiation is extremely important and can be defined as the main source for life under the Earth’s surface. Radiolysis could also be present on other celestial bodies that contain water below the surface.
Keywords: microorganisms; mikroorganizmi; nastajanje vodika; nastanek življenja; radioactivity; radioaktivnost; radioliza vode; radiolysis of water; source of life; synthesis of hydrogen